2010
DOI: 10.1258/la.2010.009115
|View full text |Cite
|
Sign up to set email alerts
|

Plasma concentrations of corticosterone and buprenorphine in rats subjected to jugular vein catheterization

Abstract: The present study investigated the postoperative plasma concentrations of corticosterone and buprenorphine in male Wistar and Sprague-Dawley rats, treated with buprenorphine administered either through subcutaneous (SC) injection or through voluntary ingestion (VI). The animals were treated with buprenorphine for pre-emptive analgesia prior to surgical placement of a jugular catheter, followed by automated blood sampling during 96 h. Buprenorphine was administered on a regular basis throughout the experiment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 27 publications
3
41
0
Order By: Relevance
“…Voluntary oral administration of analgesia is another promising approach that avoids the negative effects of handling. Several routes of oral administration have been described, such as mixing analgesics with flavored gelatine 21 , Nutella 22 , regular diet 23 or drinking water 24 . These studies in mice and rats have shown that several analgesics are efficient when administered orally and voluntarily.…”
Section: Effect Of Analgesia Protocolsmentioning
confidence: 99%
“…Voluntary oral administration of analgesia is another promising approach that avoids the negative effects of handling. Several routes of oral administration have been described, such as mixing analgesics with flavored gelatine 21 , Nutella 22 , regular diet 23 or drinking water 24 . These studies in mice and rats have shown that several analgesics are efficient when administered orally and voluntarily.…”
Section: Effect Of Analgesia Protocolsmentioning
confidence: 99%
“…Despite these concerns, several studies in mice and rats have shown that buprenorphine has sufficient analgesic efficacy when administered orally. Several routes of oral administration have been described, such as mixing buprenorphine with flavored gelatin (Liles, Flecknell et al 1998), Nutella ® (Goldkuhl, Jacobsen et al 2010, Kalliokoski, Jacobsen et al 2011, gel delivery systems (Hovard, Teilmann et al 2015) or with the regular diet of the mice (MolinaCimadevila, Segura et al 2014). …”
Section: Zusammenfassungmentioning
confidence: 99%
“…For instance, food neophobia is a well-known obstacle in the oral administration of analgesics in mice. Habituation to new food items is necessary in order to ensure sufficient intake and resulting therapeutic drug levels (Liles, Flecknell et al 1998, Goldkuhl, Jacobsen et al 2010, Kalliokoski, Jacobsen et al 2011, Hovard, Teilmann et al 2015. Moreover, even after habituation, the latency to ingestion of the drug, as well as the total amount ingested by the animals, might be difficult to anticipate (Hovard, Teilmann et al 2015).…”
Section: Zusammenfassungmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that buprenorphine administered in a sticky nut paste (Nutella w ), voluntarily ingested by laboratory rats and mice, is an effective analgesic strategy, with reduced stress and lower corticosterone levels in blood and faeces 4 -8 , and higher and prolonged buprenorphine concentrations in serum, when compared with traditional parenteral administration regimens 6,9 . However, this method is discouraged in some institutions, which is probably due to a lack of detailed instructions on how to apply the method, and uncertainty about how different animal models are affected by opioids.…”
mentioning
confidence: 99%